Cultivating organic turmeric in Sikkim - Gudade, B A; Chhetri, P; Harsha, K N; Gupta, U (Indian Horticulture, 2018)
Turmeric is widely grown and consumed spice that has got good international market demand. A large group of market participants are engaged in different activities in the entire value chain of turmeric right from production to its consumption. Prices show considerable volatility that could pose profit risk to different stakeholders. As India is having major share in the international turmeric export market, it is equally exposed to global uncertainly that affects trade time to time and thus on price. Turmeric price is quite volatile and showing marked fluctuations in daily price. Due to high volatility it reinforces the need of future trading to allow traders to hedge their risk. Other factors that indicate success of future trading is well developed spot market and a large number of participants such as traders, farmers, exporters, industrial consumer etc that provide depth and width to the market.